Black economy in India - "Arun, Kumar" (New Delhi, 1999)
In 1990-91, according to various estimates, the black economy constituted about 35 per cent of the national economy, which was larger than either its primary or secondary sectors. Since then black income generation has increased not only through both legal (real estate transactions, the share market) and illegal (hawala, financial scams, gold smuggling) activities but also via instances of corruption. The New Economic Policies expected to counter its growth have been unsuccessful in containing it. In this empirically rich and finely argued book, Arun Kumar critically examines the standard explanations for the causes and consequences of black income generation and the methods suggested for curbing it. His incisive analysis lays bare the pernicious effects of black income on the macro economy and the resultant inefficiency, waste and sub-optimality in the economy and society. It also spotlights the role of criminalization and the emerging nexus of the businessman, politician and bureaucrat in perpetuating the black economy. Showing the limited success of technical remedies like the VDIS, Arun Kumar argues in favour of structural remedial measures, which include empowering people through a right-to-information act. This revised edition has a foreword by ex-Prime Minister V.P. Singh and new appendices on employment and income in illegal activities in India and money laundering.
Keywords: Black economics